A Simplified Assessment of Factors Controlling Phosphorus Loading from Oxygenated Sediments in a Very Shallow Eutrophic Lake - Kelton N; Chow-Fraser P (Taylor & Francis, 2005)
Factors controlling the release of bioavailable soluble reactive phosphorus (SRP) from sediments in very shallow lakes are not fully understood. Our approach involved relatively simple measurements of four factors affecting the calculation of internal phosphorus load: the number of sampling sites, sediment freezing, incubation temperature and oxic state in Cootes Paradise Marsh, now a very shallow (Z = 70 cm) eutrophic degraded urban lake in Ontario, Canada. Our results indicate that all of these factors need to be considered when attempting to estimate the internal phosphorus load of a shallow system. The total internal load of phosphorus in Cootes Paradise Marsh was 34% of the total loading (both internal and external), with diffusion from the sediment accounting for 23% of all phosphorus inputs. Large carp are now excluded from the lake and were estimated by difference to have contributed 23% to summer internal loading. © 2005 Taylor & Francis Group, LLC.
Keywords: 37 Earth Sciences; 3705 Geology